L’économie politique de l’Asie : l’influence du modèle chinois et la question du rapport salarial - Pierre Alary (Revue de la Régulation)
Two lessons are clear from the transformation of Asian capitalism. First, a wide variety of national strategies to cope with price competitiveness increasingly acute. Second, the importance of the workers. Labor is the “energy” of capitalism and to maintain a strong price competitiveness, the wage-labor of the different countries is re-combine. The non-status of migrant workers in China offers to contractors a cheap labor and strengthen Chinese industry. The innovation systems also contribute to the “conquest” of the market and a comparative study (China, Korea, Japan, Taiwan) shows the specificity of national innovation models and the importance of inventors. Redefining the accumulation regime in Japan places the wage-labor to the center of the devices and industrial employment is shifting towards services.